Availability of geodata and use of open-source geotechnologies for cultural heritage. The case of Toledo (Spain) - Irene Sánchez Ondoño; Carmen García Martínez; Juan Antonio García González (Bollettino della Società Geografica Italiana, 2022)
Geotechnologies play an increasingly extensive and diverse role in our society. Their implementation in educational settings is growing at all levels, especially in higher education, and in a wide variety of disciplines. The analysis and management of cultural heritage are two of the areas where they are most used. The multiple, heterogeneous, and unspecific supply of geoinformation opens up considerable possibilities for learning and new opportunities for analysis by future specialists in cultural heritage, despite the difficulties in the management of, and approach to, the data. In a scenario in which open-source educational resources are increasingly important, this work presents an exploratory analysis of open sources of georeferenced information that facilitate access to geodata for teaching and learning on cultural heritage. As an example of the differences and shortcomings of the availability of georeferenced sources in Spain, this work presents a case study on the city of Toledo, recognised as a world heritage site.